First report of Giardia duodenalis infection in the crested porcupine (Hystrix cristata L., 1758). (April 2020) - Coppola, Francesca; Maestrini, Michela; Berrilli, Federica; Guadano Procesi, Isabel; Felicioli, Antonio; Perrucci, Stefania
Abstract: Italy is the only European country where the crested porcupine ( Hystrix cristata ) lives. A parasitological investigation was performed on faecal samples, aimed to evaluate Giardia and other parasites in a free-ranging crested porcupine population in Central Italy. Samples were collected from captured and road-killed individuals as well as from feeding areas and pathways. Collected faecal samples were examined by the Mini-FLOTAC technique and a rapid immunoassay for the search of Giardia and Cryptosporidium spp. faecal antigens. For the identification of Giardia species and genotypes, molecular analysis was performed on Giardia -positive samples, by using PCR protocols able to amplify glutamate dehydrogenase, triosephosphate isomerase and a fragment of the small subunit ribosomal RNA genes. A total of 52 crested porcupine faecal samples were collected and analysed. At microscopical examination, 39 out of 52 samples were found positive for at least a single parasite species and six different parasite taxa were identified. Forty-eight percent (25/52) of faecal samples were positive for Giardia spp. and 1.9% (1/52) for Cryptosporidium spp. at the immunoassay. Among 12 faecal samples belonging to different individuals, 33.3% (4/12) were positive for Giardia spp. By using the Mini-FLOTAC technique, positivity for Trichuris spp. (32.7%, 17/52), gastrointestinal strongyles (32.7%, 17/52), capillariid eggs (3.8%, 2/52) and coccidian oocysts (1.9%; 1/52) was also evidenced. Molecular analysis was performed on 17 out of 25 Giardia -positive isolates. At the SSU rDNA locus, expected bands were achieved for 12 out of 17 isolates and all samples were assigned to Giardia duodenalis assemblage B. Sequencing at tpi locus revealed potentially zoonotic G. duodenalis assemblage AII (two isolates) and assemblage BIV (one isolate). The present study provides the first report of G. duodenalis infection in H. cristata . More in depth studies are needed on the impact and epidemiology of G. duodenalis and other identified parasites in crested porcupines. Graphical abstract: Image 1 Highlights: Giardia and other parasites were assessed in free-ranging Hystrix cristata . Six parasite taxa were identified in 39 out of 52 examined faecal samples. Giardia duodenalis was prevalent and assemblages AII and BIV were identified. This is the first report of G. duodenalis in the crested porcupine ( H. cristata ). More studies are needed on the epidemiology of identified parasites in H. cristata .